HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI DESA NAKAMURA KECAMATAN MOROTAI SELATAN KABUPATEN PULAU MOROTAI: The Correlation Between Parenting Style and Stunting in Toddlers Aged 24-59 Months in Nakamura Village, South Morotai, Morotai Island - Trilia Romadhona; Tutik Hidayati; Muthmainnah Zakiyyah (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Parenting styles are all forms and processes of interaction that occur between parents and children and can influence the development of a child's personality. Stunting, also known as “shortness", is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life, so that children are too short for their age. The purpose of this study was to analyze the correlation  between parenting style and the incidence of stunting in toddlers aged 24-59 months in Nakamura village, South Morotai,, Morotai Island. The design of this study was correlational analysis using a cross-sectional approach. The population in this study was all mothers who had stunted toddlers aged 24–59 months in the village of Nakamura—as many as 11 people. The sample is all mothers who have stunted toddlers aged 24–59 months in Nakamura village, or as many as 11 people using the total sampling technique. The instruments used were questionnaire sheets, scales, microtois, and Z-score sheets. Of the 11 respondents, the majority had democratic parenting patterns: 5 respondents (45.5%), mothers with short stunted toddlers, 7 respondents (63.6%) with very short stunted toddlers, and 4 people (36.4%). The results of the chi-square test showed that the values of p = 0.85 and α = 0.05 where  p > α indicates that there is not correlation  between parenting style and the incidence of stunting in toddlers aged 24-59 months in Nakamura village. The results of this study are expected to provide insight to parents to further improve good parenting for children so that children's nutrition is fulfilled and there is no shortage of nutritional status in children, such as stunting.